Chitosan gold nanoparticles induce different ROS-dependent cell death modalities in leukemic cells - Martínez-Torres AC (Dove Medical Press, 2019)
Ana Carolina Martínez-Torres*, Helen Yarimet Lorenzo-Anota*, Martín Gerardo García-Juárez*, Diana G Zarate-Triviño, Cristina Rodríguez-Padilla Universidad Autónoma De Nuevo León, Facultad De Ciencias Biológicas, Laboratorio De Inmunología Y Virología, Monterrey, Nuevo Leon, Mexico*These authors contributed equally to this workCorrespondence: Ana Carolina Martínez-TorresUniversidad Autónoma de Nuevo León, Facultad de Ciencias Biológicas, Laboratorio de Inmunología y Virología, Monterrey 66455, MéxicoTel +52 8 121 4115Fax +52 818 352 4212Email ana.martinezto@uanl.edu.mxBackground: Nanotechnology proposes the use of gold nanoparticles (AuNPs) for drug delivery, diagnosis, and treatment of cancer. Leukemia is a type of hematopoietic cancer that results from the malignant transformation of white blood cells. Chitosan-coated AuNPs (CH-AuNPs) are cell death inductors in HeLa and MCF-7 cancer cells without affecting peripheral blood mononuclear cells (PBMC). Considering the selectivity and versatile cytotoxicity of CH-AuNPs, we evaluated whether their selectivity is due to the cell lineage or the characteristics of the cancer cells, by assessing its cytotoxicity in leukemic cells. Moreover, we further examined the cell death mechanism and assessed the implication of nuclear damage, autophagosome formation, and the cell death mechanism induced in leukemic cells.Materials and methods: We synthesized CH-AuNPs by chemical methods and analyzed their cell death capacity in a T-acute lymphocytic leukemia cell line (CEM), in a chronic myeloid leukemia cell line (K562), and in healthy cells from the same lineage (PBMC and bone marrow, BM, cells). Then, we assessed ROS generation and mitochondrial and nuclear damage. Finally, we evaluated whether cell death occurred by autophagy, apoptosis, or necroptosis, and the role of ROS in this mechanism.Results: We found that CH-AuNPs did not affect PBMC and BM cells, whereas they are cytotoxic in a dose-dependent manner in leukemic cells. ROS production leads to mitochondrial and nuclear damage, and cell death. We found that CH-AuNPs induce apoptosis in CEM and necroptosis in K562, both undergoing autophagy as a pro-survival mechanism.Conclusion: CH-AuNPs are selective cell death inductors in hematologic cancer cells, without affecting their healthy counterparts. Cell death induced by CH-AuNPs is independent of the cancer cell type; however, its mechanism is different depending on the type of leukemic cells.Keywords: AuNPs, leukemia, nuclear alterations, apoptosis, necroptosis, autophagy